Prediction of PWM-Induced Current Ripple in Subdivided Stator Windings Using Admittance Analysis - Antoine Cizeron; Javier Ojeda; Eric Labouré; Olivier Béthoux (Energies, 2019)
Subdividing stator winding is a way to lower the DC link voltage value in electric drives and reduce the stress on motor insulation. Coupled windings sharing the same stator teeth are modelled in order to evaluate the link between voltages disparities and current ripple. This paper provides an assessment of current ripple rise in the subdivided windings compared to ordinary topologies through the use of a basic inductive model. A method for PWM-Induced current ripple and high-frequency loss estimation based on admittance measurements is developed and experimentally validated. The use of this subdivided structure does not induce more than a 10% rise of the PWM-induced current ripple compared to a standard winding structure.